(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
In recent years, the increased consumption of high-carbohydrate diets among adolescents, particularly sugary beverages and fast foods, has led to disturbances in hormonal balance. This article analyzes the effect of hypercarbohydrate nutrition on the endocrine system of adolescents, specifically on the secretion of key hormones such as insulin, leptin, ghrelin, and cortisol. A review of the literature indicates that excessive carbohydrate intake leads to insulin resistance, disruption of leptin signaling, and hormonal imbalance, contributing to the development of metabolic syndrome. Additionally, changes in hormone levels during adolescence have been identified as early risk factors for obesity, dyslipidemia, and type 2 diabetes. The study emphasizes the need to explore the mechanisms by which hypercarbohydrate nutrition affects the endocrine system and to promote healthy eating habits among youth.